2021
DOI: 10.1002/btpr.3141
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic plants expressing a Clostridium difficile spore antigen as an approach to develop low‐cost oral vaccines

Abstract: Gastrointestinal infections caused by Clostridium difficile lead to significant impact in terms of morbidity and mortality, causing from mild symptoms, such as a lowgrade fever, watery stools, and minor abdominal cramping as well as more severe symptoms such as bloody diarrhea, pseudomembrane colitis, and toxic megacolon.Vaccination is a viable approach to fight against C. difficile and several efforts in this direction are ongoing. Plants are promising vaccine biofactories offering low cost, enhanced safety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…To this end, the CdeM protein, serving as a spore antigen, has been chosen as a carrier for mucosal immunization in vaccine development. Administration of this antigen orally has been shown to induce humoral responses against CDI in mice [ 68 ]. In the United Kingdom, Bradshaw et al found that specific traits of lipoprotein CD0873 have potential as a vaccine against C. difficile .…”
Section: Potential Application Of Immunetherapymentioning
confidence: 99%
“…To this end, the CdeM protein, serving as a spore antigen, has been chosen as a carrier for mucosal immunization in vaccine development. Administration of this antigen orally has been shown to induce humoral responses against CDI in mice [ 68 ]. In the United Kingdom, Bradshaw et al found that specific traits of lipoprotein CD0873 have potential as a vaccine against C. difficile .…”
Section: Potential Application Of Immunetherapymentioning
confidence: 99%
“…The conjugate of exosporium protein CdeM fused to the carboxy-terminus of the B subunit of the Escherichia coli heat-labile enterotoxin (LTB) was used to design a plant-based vaccine against CD. Transformed tobacco plants efficiently produced the LTB-CdeM antigen that was orally immunogenic [ 17 ]. CdeM was already shown to induce a high level of protection in CDI animal models [ 18 ].…”
Section: Targeting CD Protein Surface Componentsmentioning
confidence: 99%
“…In the other hand, recently the use of plants as bioreactors has been explored as an alternative and less expensive platform capable of incorporating transgenes and expressing heterologous proteins that are immunogenic in mice (Soria-Guerra et al 2007Brodzik et al 2009). Plants provide many advantages over recombinant mammalian systems, including the absence of potential contamination with viruses and prions, a much higher scalable capacity, and very low costs of large-scale production (Kwon and Daniell, 2016;Ward et al 2020;Rosales-Mendoza et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Plants provide many advantages over recombinant mammalian systems, including the absence of potential contamination with viruses and prions, a much higher scalable capacity, and very low costs of large-scale production (Kwon and Daniell, 2016 ; Ward et al 2020 ; Rosales-Mendoza et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%